2010
DOI: 10.1016/j.heares.2009.09.012
|View full text |Cite
|
Sign up to set email alerts
|

Pitch, harmonicity and concurrent sound segregation: Psychoacoustical and neurophysiological findings

Abstract: Harmonic complex tones are a particularly important class of sounds found in both speech and music. Although these sounds contain multiple frequency components, they are usually perceived as a coherent whole, with a pitch corresponding to the fundamental frequency (F0). However, when two or more harmonic sounds occur concurrently, e.g., at a cocktail party or in a symphony, the auditory system must separate harmonics and assign them to their respective F0s so that a coherent and veridical representation of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
89
0
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 114 publications
(99 citation statements)
references
References 111 publications
5
89
0
2
Order By: Relevance
“…The task was inspired by earlier studies involving auditory streaming and the perception of temporal relationships between sounds (van Noorden 1975;Roberts et al 2002Roberts et al , 2008Micheyl and Oxenham 2010). The general principle of these studies involves a temporal shifting of the B tones relative to the A tones in an AB or ABA stimulus sequence.…”
Section: Rationalementioning
confidence: 99%
See 1 more Smart Citation
“…The task was inspired by earlier studies involving auditory streaming and the perception of temporal relationships between sounds (van Noorden 1975;Roberts et al 2002Roberts et al , 2008Micheyl and Oxenham 2010). The general principle of these studies involves a temporal shifting of the B tones relative to the A tones in an AB or ABA stimulus sequence.…”
Section: Rationalementioning
confidence: 99%
“…Research in psychoacoustics has already led to the identification of such tasks. For instance, several studies have shown that listeners are poorer at identifying the temporal order of sounds, or detecting changes in their relative timing, if these sounds fall into separate streams than if they fall into the same stream (van Noorden 1975;Roberts et al 2002Roberts et al , 2008Micheyl and Oxenham 2010). In such tasks, therefore, stream segregation impedes performance.…”
Section: Introductionmentioning
confidence: 99%
“…Fundamental frequency (F0) information might also be expected to contribute to the reconstruction of interrupted speech, given its important role in perceptual grouping and segregation of sound sources (e.g., Bregman, 1990;Micheyl and Oxenham, 2010). However, Chatterjee et al (2010) compared recognition of interrupted noise-vocoded sentences which either had natural F0 variation or an artificially flattened F0 contour and found that while performance was affected by the number of frequency channels, the F0 contour had no effect.…”
Section: Introductionmentioning
confidence: 99%
“…Revue musicale OICRM, volume 4, n o 1 l'oreille tente de les résoudre de la même manière qu'elle le fait avec les harmoniques naturels, c'est-à-dire en recherchant une fréquence fondamentale commune aux deux sons (Micheyl et Oxenham 2010 ;Thompson 2013). L'exemple audio 6 illustre la manière dont l'harmonicité contribue à la perception de la consonance de l'intervalle de sixte mineure.…”
Section: Harmonicitéunclassified
“…Pour ce faire, nous présenterons d'abord leur modèle d'apprentissage perceptuel en mettant en évidence sa pertinence pour l'enseignement des intervalles harmoniques. Nous exposerons ensuite les principaux mécanismes perceptuels sollicités durant l'écoute des intervalles harmoniques, notamment ceux qui sont responsables de la perception des notes isolées (Oxenham 2013 ;Stainby et Cross 2009), de la friction (Lee 2011 ;Thompson 2013) et de l'harmonicité (Micheyl et Oxenham 2010 ;Thompson 2013). Enfin, en nous appuyant sur ces connaissances scientifiques, nous proposerons une nouvelle démarche d'enseignement des intervalles harmoniques qui, en amont des approches traditionnelles, visera à stimuler chez l'étudiant un véritable apprentissage perceptuel.…”
unclassified